Socio-demographic Characteristics and Mode of Traumatic Thoraco-Lumbar Spine Injuries at a Referral Tertiary Care Hospital in Bangladesh - Rahman, Md Mizanur; Rahman, Md Mahfuzur; Yusuf, Md Abdullah; Sattar, AFM Arshedi; Ali, Md Ayub; Rahman, Md Matiur; Siddique, Abu Bakar (Journal of National Institute of Neurosciences Bangladesh, 2018)
Background: Traumatic thoraco-lumbar spine injuries occur in different ways during working. Objectives: The purpose of the present study was to find out the-demographic Characteristics and Mode of Traumatic Thoraco-Lumbar Spine Injuries. Methodology: This cross-sectional study was conducted at the National Institute of Traumatology and Orthopaedic Rehabilitation (NITOR), Dhaka, Bangladesh from July 2004 to June 2006 for a period of 2(two) years. Patients with diagnosed cases of traumatic thoraco-lumbar spinal injury with complete or incomplete cord lesion irrespective of sex were selected as study population. An elaborate history of the selected patient was taken with an emphasis of mechanism, time of injury, past history of illness. Result: A total number of 17 patients with thoracolumbar spine injury were recruited. Out of 17 patients, 7(41.2%) patients were in the age group of 21-30 years that is very younger age group. The mean age was 29.29 years. The male and female ratio was 4.7:1. In this series most affected people are farmer (47.05%). Most affected groups are injured by fall from height (70.58%) especially from tree and from roof of the buildings. Conclusion: Young age group male workers are most commonly affected in traumatic thoraco-lumbar spine injuries. Journal of National Institute of Neurosciences Bangladesh, 2018;4(1): 51-53